Literasi Qurani Berbasis Teknologi: Mengintegrasikan Bahasa, Karakter, dan Digitalisasi di Rumah Tahfidz” - Indra, Novalia; Mulyadi, Jendri; Rahmawati, Elmi (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
The development of digital technology has brought about significant changes in the world of education, including in religious institutions such as Tahfidz Houses, which play a role in educating the Quranic generation through reading, memorizing, understanding, and practicing the values ​​of the Quran. However, learning activities in Tahfidz Houses still focus on reading and memorization skills, while aspects of understanding meaning, strengthening character, and utilizing technology are not yet optimal. This Community Service Program (PKM) aims to develop a model of "Technology-Based Quranic Literacy: Integrating Language, Character, and Digitalization in Tahfidz Houses." This program emphasizes improving technology-based Quranic literacy skills, language skills in interpreting Quranic values, and developing Quranic character that aligns with digital ethics. The program's implementation method includes five stages: outreach, digital literacy training, implementation of simple technology-based learning media, mentoring integrative learning practices, and evaluating the program's sustainability. This program is expected to increase the effectiveness of learning at Tahfidz houses, strengthen students' reflective abilities regarding the content of the Quran, and foster a culture of Quranic literacy that is adaptive to technological developments.